EDUKASI GIZI DALAM KESEHATAN REP EDUKASI GIZI DALAM KESEHATAN REPRODUKSI DI PONDOK PESANTREN MIFTAHUL JANNAH DESA PENINJAUAN KABUPATEN OGAN KOMERING ULU SUMSEL TAHUN 2024 - Annisa Khoiriah; Anur Rohmin; Elvina Indah Syafriani; Siti Amallia; Desi Hariani; Yessy Octa Fristika; Latifah (Ukhuwah : Jurnal Pengabdian Kepada Masyarakat, 2024)
Nutritional and reproductive health issues in adolescents are important issues that impact the quality of life and potential of the younger generation. Students in Islamic boarding schools often face challenges in the form of a lack of understanding of the importance of balanced nutrition and reproductive health due to limited access to information and lifestyle in the dormitory environment. This community service program aims to increase knowledge and awareness of the relationship between nutrition and reproductive health at the Miftahul Jannah Islamic Boarding School, Peninjauan Village, Ogan Komering Ulu Regency, South Sumatra. The method of implementing community service is mentoring, Evaluation is carried out using pre-test and post-test questionnaires to measure increased knowledge, and behavioral observation to assess the success of the program. The results of the activity showed a significant increase in students' understanding of the importance of nutrition and reproductive health, The pre-test results in community service activities showed a value of 54.33 meaning they are less aware of reproductive health education, the post-test results were 90.67 meaning effective, so that participants in community service can understand about reproductive health education training Keywords : Nutrition Education, Reproductive Health, Pre Test, Post Test.